Sosialisasi penanaman dan pemanfaatan tanaman obat keluarga (TOGA) - Nana Mardiana; Windah Anugrah Subaidah (INDRA: Jurnal Pengabdian kepada Masyarakat, 2022)
Indonesian people have used herbal plants for generations to overcome health problems, but some people are still lacking in obtaining health services. Tenggareng hamlet, North Jenggik Village, Montong Gading Dstrict, East Lombok Regency, West Nusa Tenggara Province is one of the hamlets that has not optimized the yard as land for growing herbal plants. The yard house is suitable land for planting various types of plants. The purpose of this activities was to increase the knowledge of the community, especially about the cultivation and use of medicinal plants. The method used in this community services were lecturing and discussion method. Involving 42 participants. The results of community services are increasing people knowledge and skills related to the planting and utilization of herbal plants. This can be seen from the occurrence of interactive discussions. In conclusion, by conducting socialization and utilization of Family Medicinal Plants can increase public understanding to optimize Family Medicinal Plants.